ANALISIS PENERIMAAN DAERAH DARI SEKTOR PARIWISATA KOTA SURABAYA TAHUN 2010-2014 - Rizal, Abu; Priyono, Joko (JEB17 : Jurnal Ekonomi dan Bisnis, 2016)
Every Local government strives to improve its own regional economy as Own Resource Revenue (PAD). One of the efforts is optimizing the potential economy in the tourism sector. The connection of tourism sector with local revenue is run through sharing tax or non-tax. The successful development of the tourism sector is increasing income in the reception area where tourism becomes the main component by considering some factors that influence it, such as: the number of tourist attractions on offer, the number of tourists visiting both domestic and international, and of course income per capita. And during the last 5 years, there is fluctuate contribution of tourism receipts to Own-resource Revenue (PAD). It should be able to examine the potential and factors that affect local revenues from the tourism sector beside improving facilities that can support the activities of tourists during a visit in a tourist attraction. Quantitative method is used by researcher in type and source the data with secondary observation period 2010-2014. The research variables consist of regional revenue dependent variable (Y), The number of independent variables, Tourism Object (X1), The number of tourists (X2) and Income Per Capita(X3). Multiple linear regression, t-test, f and the coefficient of determination are used as method of collecting data. Based on the results of multiple linear regression analysis, the results are : Y = -3,342E13 + 3,657E10 166,168.483 X1 + X2 + X3 + e 3,080E9. It also find the value t of tourism amounted to 15.115, the number of tourists amounted to 14.110 andincome percapita amounted to 13.099 t 2.13185 table. As for testing simultaneously or jointly acquired 217.657 F count> F table 216. Thus H0 is rejected and Ha is accepted. The conclusion from this study indicates that the amount of tourism attraction, the number of tourists and the income per capita in partial and simultaneously have positive and significant influence to Own Resource Revenue in Surabaya. While the number of tourists variable X2 is a variable that is the most dominant in the reception area of Surabaya in tourism sector.Keywords: PAD, Surabaya City, Tourism Sector, Tourism Industry